Abandoning developmental silos: what can paediatricians and adult interstitial lung disease physicians learn from each other?. Issue 5 (September 2019) - Spagnolo, Paolo; Griese, Matthias; Cocconcelli, Elisabetta; Bernardinello, Nicol; Bush, Andrew
Abstract : Purpose of review: Interstitial lung disease (ILD) consists of a large and heterogeneous group of disorders that are classified together because of similar clinical, radiographic, physiologic or pathologic manifestations. Overall, although there is overlap between adult and childhood ILD (chILD), there are many differences in disease causes and prevalences. Recent findings: In the last few years, our understanding of adult ILD pathobiology has improved substantially. This is particularly true for idiopathic pulmonary fibrosis, the most common of the idiopathic interstitial pneumonias, wherein recently developed guideline documents provide recommendations for the diagnosis and clinical management of patients. For chILD, similar guidelines are yet to be developed. However, complications and long-term pulmonary outcomes of paediatric disease are better appreciated, which make the implementation of a successful transition program from paediatric to adult care an urgent need. Similarly important is the development of guidelines on performance and interpretation of genetic testing in affected and unaffected relatives of familial cases and in children of adult-onset ILD patients. Lung transplantation appears to be as successful as in adult patients for end-stage disease. Paediatric pulmonologists should engage with the adult multidisciplinary teams and benefit from their much more extensive experience. Summary: Childhood and adult ILD share a number of aspects, which give children and adult ILD specialists exciting opportunities to collaborate and learn from each other. Such collaborative effort between child and adult ILD experts is crucial for successful future development in the field.